Determinant Analysis of Business Risk with Institutional Ownership as a Moderating Variable - Nofrialdi, Reski; Saputra, Farhan; Mahaputra, M. Ridho (Siber International Journal of Digital Business (SIJDB), 2023)
The purpose of this study was to determine the effect of the level of institutional ownership on the relationship between asset quality, leverage, efficiency, BI rate and business risk. The method used in this study is explanatory research. Data analysis in this study is the normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. From the results of the research that has been done, several conclusions are obtained as follows: Asset quality has no significant negative effect on business risk. Leverage has a significant negative effect on business risk. Efficiency has a significant positive effect on business risk. BI rate has no significant negative effect on business risk. Institutional ownership has no effect on the relationship between asset quality, leverage, efficiency and business risk.